PENGUKURAN PEMAHAMAN MASYARAKAT TERHADAP ISTILAH TERKAIT PANDEMI COVID-19 DENGAN MENGGUNAKAN TEORI HIMPUNAN - Tyla Safitri Widianingrum; Faradhiba Salsabila; Bayu Setiawan; Raihan Dzul Pahlevi; Nani Darmayanti (Jurnal Semantik, 2022)
Many of the new terms that emerged during the Covid-19 pandemic are important for the public to understand because they are the key to preventing the Covid-19 virus. Therefore, it is very important to measure people's understanding of the terms that emerged during the Covid-19 pandemic. The purpose of this study was to determine the classification of the term Covid-19 pandemic and understan the level of public understanding regarding the term Covid-19 pandemic. This study uses a combined method that combines quantitative and qualitative research methods. Combined methods can make the results of the analysis more comprehensive. The data in this study were obtained through a questionnaire which was then processed using descriptive statistical methods and visualized using bar charts and venn diagram. The results of this study indicate that terms that are easily understood by the public related to the Covid-19 pandemic are terms in the form of basic words and come from the absorption of the term.